Terpenoids from Glechoma hederacea var. longituba and their biological activities - Kim, Dong Hyun; Ham, Song Lim; Khan, Zahra; Kim, Sun Yeou; Choi, Sang Un; Kim, Chung Sub; Lee, Kang Ro (Beilstein Journal of Organic Chemistry, 2022)
Glechoma hederacea var. longituba (common name: ground ivy) has been used for the treatment of asthma, bronchitis, cholelithiasis, colds, and inflammation. In the present study, three new sesquiterpene glycosides (1–3), two new diterpene glycosides (4 and 5), and four known compounds (6–9) were isolated from its MeOH extract. A structure elucidation was performed for the five new compounds (1–5) using 1D and 2D NMR, HRESIMS, DP4+ and ECD calculations, and chemical methods. All the isolates (1–9) were assessed for their antineuroinflammatory activities on nitric oxide (NO) production in lipopolysaccharide (LPS)-activated BV-2 cells, nerve growth factor (NGF) secretion stimulation activities in C6 glioma cells, and cytotoxic activities against four human cancer cell lines (A549, SK-OV-3, SK-MEL-2, and HCT15). Compounds 2 and 5–7 exhibited inhibitory effects on the NO production with IC50 values of 52.21, 47.90, 61.61, and 25.35 μM, respectively. Compound 5 also exhibited a significant stimulating effect on NGF secretion (122.77 ± 8.10%). Compound 9 showed potent cytotoxic activity against SK-OV-3 (IC50 = 3.76 μM) and SK-MEL-2 (IC50 = 1.48 μM) cell lines, while 7 displayed a strong cytotoxic activity against the SK-MEL-2 (IC50 = 9.81 μM) cell line.
Keywords: antineuroinflammation; cytotoxicity; Glechoma hederacea var. longituba; neurotrophic effect; terpenoid